Optimizing PCR positivity criterion for detection of herpes simplex virus DNA on skin and mucosa - Magaret, Amalia S; Wald, Anna; Huang, Meei-Li; Selke, Stacy; Corey, Larry (Journal of clinical microbiology, 2007)
In 1997, we developed a PCR assay for the detection of herpes simplex virus (HSV) DNA. Recently, we determined an optimal positivity criterion based on research specimens and a dilution study. We found that a cutoff of 50 HSV DNA copies/ml of swab specimen, a level 10-fold lower than our previous cutoff, minimizes misclassification.